The Diagnosis of Urinary Tract Infection: A Systematic Review - Schmiemann, Guido (Deutscher Arzte Verlag, 2010)
BACKGROUND: Urinary tract infections (UTI) are among the leading reasons for treatment in adult primary care medicine, accounting for a considerable percentage of antibiotic prescriptions. Because this problem is so common and so significant in routine clinical practice, a high level of diagnostic accuracy is essential. Antibiotics should not be prescribed excessively, particularly in view of the increasing prevalence of antibiotic resistance. METHOD: Systematic review of relevant articles that were retrieved by a search of the Medline, Embase, and Cochrane Library databases. The recommendations of selected international guidelines were also taken into account, as were the German national quality standards for microbiological diagnosis. RESULTS: The diagnosis of UTI by clinical criteria alone has an error rate of approximately 33%. The use of refined diagnostic algorithms does not completely eliminate uncertainty. CONCLUSION: With the aid of a small number of additional diagnostic criteria, antibiotic treatment for UTI can be provided more specifically and thus more effectively. Differentiating UTI from asymptomatic bacteriuria, which usually requires no treatment, can lower the frequency of unnecessary antibiotic prescriptions.